2019
DOI: 10.1123/jsr.2018-0384
|View full text |Cite
|
Sign up to set email alerts
|

The Quantification of Hop Landing Balance Using Trunk-Mounted Accelerometry

Abstract: Context: Balance is important for injury prediction, prevention, and rehabilitation. Clinical measurement of higher level balance function such as hop landing is necessary. Currently, no method exists to quantify balance performance following hopping in the clinic. Objective: To quantify the sacral acceleration profile and test–retest reliability during hop landing. Participants: A total of 17 university undergraduates (age 27.6 [5.7] y, height 1.73 [0.11] m, weight 74.1 [13.9] kg). Main Outcome Measure: A tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…This corroborated the 1-week and 6-month excellent reliability in detecting PTA during running with the same device 10 and represented improved reliability than that reported for detecting the landing hop phase with a trunk accelerometer. 6 Interestingly, the reliability of SS fixation was slightly improved for determining the peak tibial AS than DST. One possible explanation for this difference is that the SS Velcro may allow the device to be iteratively adjusted to tolerance, which is more difficult than DST.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This corroborated the 1-week and 6-month excellent reliability in detecting PTA during running with the same device 10 and represented improved reliability than that reported for detecting the landing hop phase with a trunk accelerometer. 6 Interestingly, the reliability of SS fixation was slightly improved for determining the peak tibial AS than DST. One possible explanation for this difference is that the SS Velcro may allow the device to be iteratively adjusted to tolerance, which is more difficult than DST.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Body-worn inertial measurement units (IMUs) have been utilized to establish a strong correlation between tibial acceleration and peak landing forces during a vertical jump 5 ; however, only one study has reported on their use during SLH. 6 Using a trunkmounted accelerometer via double-sided tape (DST), Williams et al 6 reported that a measure of postural sway to quantify hop landing balance had moderate-to-excellent reliability. 6 The integrity of fixation between accelerometer and body influences the measurement signal because of noise introduced from device resonance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, an inertial measurement units (IMU) device with an accelerometer (WIMU, Realtrack Systems, Almeria, Spain: weight: 70 g, size: 81 mm x 45 mm x 16 mm) was placed to all the athletes using an adjustable sports lycra belt, which fixed the device at the back of the waist, at L4-5 level. This position provided the best information about the movement of the whole body, as the location is close to the centre of mass [ 15 , 27 ]. The IMU was set to a sampling frequency of 1000 Hz, and it was calibrated on a flat and even surface with the z-axis perpendicular to the surface.…”
Section: Methodsmentioning
confidence: 99%
“…To date, the measurement of the effects of destabilising devices has been addressed through different parameters as EMG activity [ 1 , 21 , 22 ], external load moved in different exercises [ 4 ], movement time and amplitude [ 23 ], movement speed [ 24 , 25 ], displacement of the centre of pressures and acceleration of the centre of mass measured trough a force plate [ 6 ], kinetic and kinematic variables captured from 3D movement analysis [ 26 ] or trunk acceleration [ 15 , 16 , 27 29 ]. Regarding trunk acceleration, several authors used accelerometers placed in the lower back to measure different tasks [ 27 , 28 ] and found high correlation with balance measures obtained through force plates [ 30 ]. Most analyses have been done using measurements for linear systems, which quantify the magnitude of variations in a time series.…”
Section: Introductionmentioning
confidence: 99%